The impact of baryons on the direct detection of dark matter. Issue 8 (31st August 2016) - Kelso, Chris; Savage, Christopher; Valluri, Monica; Freese, Katherine; Stinson, Gregory S.; Bailin, Jeremy
Abstract: The spatial and velocity distributions of dark matter particles in the Milky Way Halo affect the signals expected to be observed in searches for dark matter. Results from direct detection experiments are often analyzed assuming a simple isothermal distribution of dark matter, the Standard Halo Model (SHM). Yet there has been skepticism regarding the validity of this simple model due to the complicated gravitational collapse and merger history of actual galaxies. In this paper we compare the SHM to the results of cosmological hydrodynamical simulations of galaxy formation to investigate whether or not the SHM is a good representation of the true WIMP distribution in the analysis of direct detection data. We examine two Milky Way-like galaxies from the MaGICC cosmological simulations (a) with dark matter only and (b) with baryonic physics included. The inclusion of baryons drives the shape of the DM halo to become more spherical and makes the velocity distribution of dark matter particles less anisotropic especially at large heliocentric velocities, thereby making the SHM a better fit. We also note that we do not find a significant disk-like rotating dark matter component in either of the two galaxy halos with baryons that we examine, suggesting that dark disks are not a generic prediction of cosmological hydrodynamical simulations. We conclude that in the Solar neighborhood, the SHM is in fact a good approximation to the true dark matter distribution in these cosmological simulations (with baryons) which are reasonable representations of the Milky Way, and hence can also be used for the purpose of dark matter direct detection calculations.